2012
DOI: 10.1053/j.ajkd.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in Individuals With CKD

Abstract: There are few studies evaluating exercise in the nondialysis chronic kidney disease (CKD) population. This review covers the rationale for exercise among patients with CKD not requiring dialysis and the effects of exercise training on physical functioning, progression of kidney disease, and cardiovascular risk factors. In addition, we address the issue of the risk of exercise and make recommendations for implementation of exercise in this population. Evidence from uncontrolled studies and from small randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
191
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(211 citation statements)
references
References 43 publications
4
191
1
8
Order By: Relevance
“…A very important factor related to outcome in CKD patients is PA, and it is well known that exercise on a regular basis is beneficial for CKD patients [74][75][76]. It has been shown that sedentary HD patients have a 62% higher mortality risk compared with non-sedentary HD patients.…”
Section: Ckd In Connection With Fitness/frailty-related Parameters (1mentioning
confidence: 99%
See 1 more Smart Citation
“…A very important factor related to outcome in CKD patients is PA, and it is well known that exercise on a regular basis is beneficial for CKD patients [74][75][76]. It has been shown that sedentary HD patients have a 62% higher mortality risk compared with non-sedentary HD patients.…”
Section: Ckd In Connection With Fitness/frailty-related Parameters (1mentioning
confidence: 99%
“…It has been shown that sedentary HD patients have a 62% higher mortality risk compared with non-sedentary HD patients. Previous studies already advocated that PA programs should be routinely implemented in patient care for CKD/ESRD patients since results showed strong associations between regular exercise and better HRQOL scores, higher muscle mass, better physical functioning, and longer survival [75,[77][78][79] (see also Figure 8). …”
Section: Ckd In Connection With Fitness/frailty-related Parameters (1mentioning
confidence: 99%
“…However much of this research was conducted in the dialysing population. Johansen & Painter [22] reviewed the research regarding exercise specifically in predialysis CKD and found a limited evidence base but could identify positive trends towards improved physical functioning for patients when the level of physical activity increased. A subsequent meta-analysis [21] investigated the research regarding exercise in CKD, separated into pre-RRT patients, RRT patients and transplant patients and concluded there was a dearth of good quality research investigating pre-RRT patients.…”
Section: What Are the Health Benefits Of Exercise In Ckd?mentioning
confidence: 99%
“…Patients with advanced CKD have a comparable burden of patientreported symptoms, including fatigue, poor sleep, depression, and poor overall health-related quality of life (HRQOL), as those with dialysis-dependent ESRD (1). Moreover, patients with CKD commonly have poor physical function and frailty, conditions that lead to poor outcomes, including falls and hospitalizations (2,3). Patient-reported and physical functioning outcomes are not only important indicators of morbidity and functional independence, but may also have prognostic significance in terms of mortality risk (4)(5)(6).…”
mentioning
confidence: 99%
“…Reasons for the paucity of studies in CKD may include concerns about safety, specifically BP and glycemic control, as well as the only recent recognition of nondialysis CKD as a clinically important disease state (3). In this context, Rossi et al conducted one of the largest clinical trials to date evaluating the safety and efficacy of a supervised exercise program in people with CKD, which is published in this issue of CJASN (8).…”
mentioning
confidence: 99%